Do Community Development Projects, Employee Training, and Educational Disclosures Influence Corporate Performance of Listed Firms in Sub-Sahara Africa? - MIESEIGHA, Ebipanipre Gabriel (UW Journal of Management Sciences, 2024)
Purpose: Corporate firms have been contending to better their performance in diverse measures without considering the effects of their actions on other stakeholders, such as employees and members of host community. This resulted to increased corporate failure which necessitated agitations from national and international organizations demanding that corporate firms disclose expenditures on social costs. This study investigates the effect of community development and employee training disclosures on corporate performance in Nigeria, South Africa, Botswana, and Kenya. Design and Methodology: Ex-post facto research design was employed and secondary data obtained from the yearly published financial statements of the selected countries from 2021-2022. Corporate performance metrics used were return on equity and return on asset while the metrics for social accounting adopted in this study were disclosures on community development projects and employee training and educational costs. Collected data obtained were analyzed using multiple regression models. Findings: Findings revealed that return on asset for Nigerian enterprises under community development project disclosure is negligible. The study further confirmed a positive but insignificant influence on return on assets for firms in South Africa and Botswana, while a significant effect was found for firms in Kenya. On the other hand, it was found that employee training and educational disclosure has insignificant effect on return on equity of firms in Nigeria, South Africa and Botswana while a significant effect of employee training and educational disclosure on return on equity was found for firms in Kenya. Implications: The results implied that publicly traded firms in Nigeria, South Africa and Botswana need to focus more attention on other components of social accounting disclosures while firms in Kenya are encouraged to increase their level of social disclosures on community development projects as well as employee training and educational disclosures to boost corporate performance. Keywords: Social accounting; Corporate performance, Community development projects disclosure; Training/development disclosure